Time-resolved decoding of planned delayed and immediate prehension movements. (February 2018) - Ariani, Giacomo; Oosterhof, Nikolaas N.; Lingnau, Angelika
Abstract: Different contexts require us either to react immediately, or to delay (or suppress) a planned movement. Previous studies that aimed at decoding movement plans typically dissociated movement preparation and execution by means of delayed-movement paradigms. Here we asked whether these results can be generalized to the planning and execution of immediate movements. To directly compare delayed, non-delayed, and suppressed reaching and grasping movements, we used a slow event-related functional magnetic resonance imaging (fMRI) design. To examine how neural representations evolved throughout movement planning, execution, and suppression, we performed time-resolved multivariate pattern analysis (MVPA). During the planning phase, we were able to decode upcoming reaching and grasping movements in contralateral parietal and premotor areas. During the execution phase, we were able to decode movements in a widespread bilateral network of motor, premotor, and somatosensory areas. Moreover, we obtained significant decoding across delayed and non-delayed movement plans in contralateral primary motor cortex. Our results demonstrate the feasibility of time-resolved MVPA and provide new insights into the dynamics of the prehension network, suggesting early neural representations of movement plans in the primary motor cortex that are shared between delayed and non-delayed contexts.